Analysis of the Credibility of the Abbasid Caliphs as Rāwī Hadith: The Relationship between Power and Knowledge in the Perspective of Naqd al-Hadith - Niam Masruri, Ulin; Soebahar, Moh Erfan; Mufid, Abdul; Sya’roni, Mokh. (Institut Agama Islam Negeri (IAIN) Curup, 2025)
This study bridges the gap in previous research, which has discussed Abbasid politics from a historical perspective but has not systematically examined their position as hadith narrators. This study contributes new insights into how power influences trust in sanad and the acceptance of narrations. The credibility of hadith narrators is a crucial factor in determining the quality of a hadith, as the acceptance or rejection of information depends on their reliability. In this context, the Abbasid Caliphs as hadith narrators are often debated regarding their credibility. This study aims to analyze the credibility of the Abbasid Caliphs as hadith narrators and their influence on their transmission of hadith. This study uses the naqd al-Hādīs method with descriptive narratives and Foucault's theory of power relations. The results reveal that the credibility of the Abbasid Caliphs as narrators of hadith is majhūl al-ḥāl (unknown status). The integrity of the critics is maintained, preventing a correlation between knowledge and power.